Beyond affordable shelters: Subsidized housing and surrounding environments for pedestrian safety. (June 2017) - Woo, Ayoung; Yu, Chia-Yuan
Abstract: Beyond the provision of affordable housing itself, planners and policymakers have raised concerns as to whether subsidized housing developments provide "suitable living environments" for the nation's poor. Despite numerous concerns regarding unfavorable living environments and the neighborhood context of subsidized housing, we have limited understanding as to whether built environments around subsidized housing ensure pedestrian safety. This study addressed this gap by examining how built environments around Low Income Housing Tax Credit (LIHTC) sites affect pedestrian-vehicle crashes in Austin, Texas. We employed the two-level negative binomial regression to clarify the impacts of street segment-level and neighborhood-level built environments on pedestrian crashes around LIHTC complexes. We found that higher speed roads, traffic-generating land uses, higher transit stop densities, and higher four-or-more-leg intersection densities may hinder pedestrian safety. Conversely, local roads as well as single-family residential parcels and connected sidewalks along street segments may enhance pedestrian safety around LIHTC complexes. Our results may inform planners and policymakers on how to enhance pedestrian safety for subsidized housing by modifying surrounding environments and how to provide better site selection considerations for subsidized housing to ensure pedestrian safety. Highlights: Higher speed roads, traffic-generating land uses, higher transit stop densities, and higher four-or-more-leg intersection densities may hinder pedestrian safety. Local roads as well as single-family residential parcels and connected sidewalks along street segments may enhance pedestrian safety around LIHTC complexes. Results inform planners and policymakers on how to enhance pedestrian safety for subsidized housing.